Obtenção do óleo de sementes dos frutos do cerrado pequi (Caryocar brasiliense Camb) e murici (Byrsonima crassifolia) utilizando diferentes solventes no processo de extração - Araújo, Ana Cristina Moreira Andrade (2016)
A significant number of fruit species of the Brazilian Midwest are still little exploited taking into account the diversity of applications that the products and by-products coming from these fruits can have. It is highly important to know about the chemical characterization and the bioactive compounds from every part of the fruit (fruit peel, pulp and seed), because the disposal of the unutilized parts, including the seeds, generates a lot of waste to the environment. Find new alternatives of use to these waste become interesting because not only can decrease the amount of waste being generated but also adds more value to it. This work had as an objective characterize the pequi’s (Caryocar brasiliense) and Murici’s (Byrsonima crassifolia) seeds and evaluate the oil extraction efficiency in them, using different kinds of organic solvents (ethanol, hexane, isopropanol and acetone) and its mixes, always having ethanol as a main solvent in the mix, putting into different temperatures (35°C, 45°C and 55°C) and using the mass ratio seed:solvent of 1:5. The analyses of thermodynamic parameters in the extraction process were realized. The characterization of the seeds has shown that they are good sources of lipids and phenolic compounds. Higher efficiency in the extraction of soluble solids in the seed was discovered using hexane and temperature of 55°C. The use of hexane in the ethanol solvent solution, and the increase of the temperature had a positively influence at the extraction process. The thermodynamic analysis of the data reported in positive ΔH e ΔS and negative ΔG, showing that the extractions processes were endothermic and spontaneous.